PENGOLAHAN LENGKUAS MENJADI LENGKUAS BUBUK UNTUK MENGOPTIMALKAN PEMANFAATAN LENGKUAS DI DESA PENIMBUNG, KEC. GUNUNG SARI, LOMBOK BARAT - Nafis, Rafidatun; Oktaviani, Arida; Febrianti, Devi; Maulida, Putri; Sukarso, AA. (Universitas Mataram, 2023)
Penimbung Village is one of the galangal producing villages in Gunungsari District. West Lombok Regency. Galangal or galangal is a type of spice that is often used in Indonesian food. The problems faced by galangal farmers in Penimbung Village are the low selling price of galangal, the lack of innovation in galangal processing and the rapid decline in harvest quality caused by pests resulting in blackened and dried (damaged) galangal. Based on the potential and existing problems, new innovations are needed in galangal processing which can increase the price and durability of galangal by processing galangal into powdered galangal which has a long shelf life. The galangal powder produced consists of two variants, namely fine galangal powder and coarse powdered galangal. The resulting galangal is packaged using a standing pouch so that it is easier to store, hygienic and more practical to use. In addition, packaging also serves to increase the economic value of the product. The study results of galangal contain terpenoid compounds such as galanoklaton, 16-dial, 12-labdiene-1510.25 Galanoklaton, 16-dial, 12-labdiene-15 which is classified as a diterpene and 1.8 cineol which is a monoterpene group. These compounds function to give a distinctive aroma to dishes and eliminate fishy odors in several types of dishes. Galangal is a medicinal plant that contains antimicrobial diterpenes and eugenol which can kill fungi and stop their growth. Traditionally, galangal rhizome is used as a medicine for skin diseases caused by fungi, such as ringworm, scabs, boils, and others. This innovation is expected to be a solution to the problems faced by galangal farmers in Penimbung Village.